Densification of LaGaO3 at low sintering temperatures via Fe3+ substitution at Ga3+ site - Chandrasekaran, A.; Azad, A.-M. (Springer Netherlands, 2001)
Attempts to achieve near theoretical density in polycrystalline LaGaO3 compacts using Fe2O3 as a dopant have been made. The B-site substituted lanthanum gallates with iron doping ranging from 15 to 55 mole% FeO1.5 (Fe2O3) were synthesized via solid state reaction using oxide and nitrate precursors and sintered at 1200°C for 24 to 72 h and at 1300°C for 12 to 36 h. Systematic variation in the lattice constants and microstructural aspects was followed as a function of mole fraction of Fe2O3. It was found that the parent LaGaO3 structure could take up as high as 55 mole% of Fe2O3 retaining the orthorhombic crystal structure. Compositions containing 35 mole% Fe2O3 soaked for 48 h or more at 1200°C and for as low as 12 h at 1300°C resulted in perfectly dense compacts. Bodies containing lower dopant concentrations (xFe2O3 ≤ 0.25) were found to have a substantial degree of porosity with good intergranular connectivity, while a significant amount of grain growth and broad grain size distribution was an interesting feature in samples containing mole fractions higher than 0.35.